Performance Evaluation of Digital Back-Propagation in the Presence of Power Excursion - Huang, Xiatao; Yi, Xingwen; Jin, Taowei; Zhang, Jing; Xu, Bo; Li, Fan (IEEE photonics technology letters, 2021)
An accurate power map is mandatory to evaluate the performance of optical fiber transmissions in the nonlinear transmission region. In this letter, we discuss the performance variation in dispersion unmanaged fiber links due to power excursions, overarching the fiber nonlinearity that imposes a fundamental limit on the capacity of optical fiber transmissions. After using digital back-propagation (DBP) in optical fiber transmissions, the performance degradation due to power excursions shows different characteristics, depending on the location of the power excursion. Further, due to the cascading effect of the nonlinear signal-noise interaction (NSNI), the power excursion on the latter spans exerts a greater impact than that on the front spans. We implement a polarization-multiplexed 16-QAM over 12 spans of standard single-mode fiber (SSMF) experiment. The experimental results verify our theoretical analyses that the received SNRs after DBP can be sensitive to the power excursion and its location.